Attempt 1 of
For the following system, use the second equation to make a substitution for y in the first equation.
3x + y = 1
y+4= 5x
What is the resulting equation?
3x + 5x + 4 = 1
3x + 4 - 5x=1
3x + 5x - 4 = 1
NEXT QUESTION
TURN ITIN
ASK FOR HELP
https://cabarruscsd.owschools.com/owsoo/student Assignment/index?eh-795134676
ka
O

Respuesta :

Answer:

3x + 5x - 4 = 1

Step-by-step explanation:

rewrite equations (i'm using the substitution method)

3x + y = 1

y = 5x − 4

plug in the second equation into the first

3x + (5x − 4) = 1

ACCESS MORE